Yearning for the Lost Paradise: The "Great Unity" (datong) and Its Philosophical Interpretations - Bart DESSEIN (Asian Studies, 2017)
In the course of China’s history, the term datong (great unity) has been interpreted in multiple ways. This article first discusses the concept as understood in the Liji, and then focuses on the way in which the perceived loss of the “great unity” within “all-under-heaven” (tianxia) at the end of the Qing dynasty (1644–1911), and the endeavor to reconstruct the empire as a modern nation-state starting in the early twentieth century, informed the way the term datong was interpreted. After discussing the interpretations by Wang Tao (1828–1897), Hong Xiuquan (1813–1864), Kang Youwei (1858–1927), Liang Qichao (1873–1929), Sun Zhongshan (1866–1925), and Mao Zedong (1893–1976), this work concludes with a discussion on how, against the background of the perceived threat of loss of national unity that characterizes the contemporary People’s Republic of China, a New Confucian interpretation is developed.